2019
DOI: 10.1029/2019gc008219
|View full text |Cite
|
Sign up to set email alerts
|

How Do Variably Striking Faults Reactivate During Rifting? Insights From Southern Malawi

Abstract: Crustal extension is commonly thought to be accommodated by faults that strike orthogonal and obliquely to the regional trend of the minimum compressive stress (σ3). Activation of oblique faults can, however, be conceptually problematic as under Andersonian faulting, it requires preexisting crustal weaknesses, high fluid pressures, and/or stress rotations. Furthermore, measurements of incremental fault displacements, which are typically used to identify oblique faulting, do not necessarily reflect regional str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
137
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(148 citation statements)
references
References 97 publications
(315 reference statements)
10
137
1
Order By: Relevance
“…An extension azimuth of 072° is recorded geodetically at Zomba (Figure ; Stamps et al, ) in contrast to the NW‐SE extension in the Zomba Graben. This variation in extension direction is consistent with previous observations of deviation between local and regional extension directions in Malawi (Delvaux & Barth, ; Hodge et al, ; Williams et al, ).…”
Section: Active Faults Within the Zomba Grabensupporting
confidence: 92%
See 4 more Smart Citations
“…An extension azimuth of 072° is recorded geodetically at Zomba (Figure ; Stamps et al, ) in contrast to the NW‐SE extension in the Zomba Graben. This variation in extension direction is consistent with previous observations of deviation between local and regional extension directions in Malawi (Delvaux & Barth, ; Hodge et al, ; Williams et al, ).…”
Section: Active Faults Within the Zomba Grabensupporting
confidence: 92%
“…This contradicts previous rift‐wide estimates of extension (Delvaux & Barth, ; Figure ). However, these estimates likely reflect that normal faulting events in the Malawi Rift are approximately purely dip‐slip despite regional changes in fault strike (Williams et al, ), as also indicated by the 2009 Karonga earthquakes (Biggs et al, ), the 1989 Salima earthquake (Jackson & Blenkinsop, ), and a M w = 5.6 earthquake in March 2018 (red focal mechanism in Figure b). An extension azimuth of 072° is recorded geodetically at Zomba (Figure ; Stamps et al, ) in contrast to the NW‐SE extension in the Zomba Graben.…”
Section: Active Faults Within the Zomba Grabenmentioning
confidence: 94%
See 3 more Smart Citations